Challenges facing village land councils in managing land disputes. A case of Girango Division in Rorya district - Marwa, John (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirements for the award of Master of Science in Human Resource Management (MSc-HRM) of Mzumbe University